Analisis pengaruh promosi dan kualitas pelayanan terhadap kepuasan pelanggan pada objek wisata puncak gundaling di Kabupaten Karo - Milala , Bryan Joriko S; Fakhri, Mahendra (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Gundaling Peak is a tourist attraction located in the Karo highlands. To increase the number of visitors, customer satisfaction must be considered and improved, several variables that can affect customer satisfaction include promotion and service quality. This study aims to analyze the impact of promotion and service quality on customer satisfaction who visit the Puncak Gundaling tourist attraction. The method used in this research is a descriptive quantitative research method and the sampling technique is non-probability sampling with a total of 100 respondents. Data collection techniques are questionnaires and library data collection. The conclusion of this study is that promotion and service quality affect visitor satisfaction with a percentage of 65.77% and the remaining 34.23 is influenced by other variables not examined in this study.